Reaktivitas Sesar Kaligarang, Semarang - Poedjoprajitno, S.; Wahyudiono, J.; Cita, A. (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no3.20082Kaligarang Fault which cuts across Semarang City in a north-south direction has been activated for long periods. During Tertiary time, the Kaligarang Fault experienced a dextral wrench movement, which was triggered by a tectonic activity during that time, with a maximum principal stress (Ï 1) in a northeast - southwest direction. While on Quaternary time, this fault was reactivated as a sinistral wrench fault. Reactivation of this fault was caused by a principal stress (Ï 2) in a north east - south last direction. Â  Â